Priority is to have better varsities says Najib - The Star, Simon Khoo (2009)
No new universities will be built as the prsent 41, including private institutions of higher learning, are adequate, said Deputy Prime Minister Datuk Seri Najib Tun Razak. Instead, he said, the priority would be to improve the existing universities.